2020
DOI: 10.3390/genes11040374
|View full text |Cite
|
Sign up to set email alerts
|

Complex Structure of Lasiopodomys mandarinus vinogradovi Sex Chromosomes, Sex Determination, and Intraspecific Autosomal Polymorphism

Abstract: The mandarin vole, Lasiopodomys mandarinus, is one of the most intriguing species among mammals with non-XX/XY sex chromosome system. It combines polymorphism in diploid chromosome numbers, variation in the morphology of autosomes, heteromorphism of X chromosomes, and several sex chromosome systems the origin of which remains unexplained. Here we elucidate the sex determination system in Lasiopodomys mandarinus vinogradovi using extensive karyotyping, crossbreeding experiments, molecular cytogenetic methods, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…At first, the hypothesis of a Y-loss in L. mandarinus seems in total contradiction with the description of males with heterogametic sex chromosomes. However, chromosome painting analyses revealed that the sex chromosomes have fused with autosomes [84], and segregation studies show that one chromosome segregates as expected from a Y [85]. Whether this chromosome consists of the association of the ancestral Y (whole or fragmented) and a neo-Y, or is just composed of a neo-Y (following complete loss of the ancestral Y) remains to be determined.…”
Section: Lasiopodomys Mandarinusmentioning
confidence: 99%
See 2 more Smart Citations
“…At first, the hypothesis of a Y-loss in L. mandarinus seems in total contradiction with the description of males with heterogametic sex chromosomes. However, chromosome painting analyses revealed that the sex chromosomes have fused with autosomes [84], and segregation studies show that one chromosome segregates as expected from a Y [85]. Whether this chromosome consists of the association of the ancestral Y (whole or fragmented) and a neo-Y, or is just composed of a neo-Y (following complete loss of the ancestral Y) remains to be determined.…”
Section: Lasiopodomys Mandarinusmentioning
confidence: 99%
“…For simplicity, we will refer to this chromosome as the "Y" thereafter. Based on crossbreeding experiments, Romanenko et al studied the transmission patterns of sex and neo-sex chromosomes and revised the sex-determining system of the mandarin vole: they describe one type of males (heterogametic), and three distinct female "karyomorphs": a homogametic one, a heterogametic one with the two morphologically different Xs, and a heterogametic one with the female specific X and the Y [85]. As mentioned by the authors, the pattern of association between phenotypic sex and sex chromosome combinations is highly reminiscent of the ones found in other rodents with X*Y females, and the change in sex determination of the mandarin vole fits well with the existence of an X-linked feminizing mutation.…”
Section: Lasiopodomys Mandarinusmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, there are species in which fertile XY females live alongside the standard XX females and XY male. Naturally occurring XY sex-reversal has evolved at least five times independently: twice in lemmings, in the wood and collared lemmings Myopus schisticolor and Dicrostonyx torquatus (5, 6), in several species of South American field mice of the genus Akodon (7, 8), in the African pygmy mouse Mus minutoides (9), and in the Mandarin vole Lasiopodomys mandarinus (10, 11). In all these rodents, sex-reversal is due to a feminizing mutation on the X, rather than a loss of function of the Y.…”
Section: Introductionmentioning
confidence: 99%
“…As for sex chromosome evolution in mammals, Romanenko and collaborators [27] present the intriguing case of the mandarin vole (Lasiopodomys mandarinus), characterized by a complex sex chromosome system (neo-Xs). In their study, the authors provide a comprehensive view of this species combining conventional and molecular cytogenetic methods, single chromosome DNA sequencing, and breeding experiments, revealing the chromosome segregation pattern as well as the reproductive performance of different karyomorphs.…”
mentioning
confidence: 99%